Correlation of Angiogenic Biomarkers to Tumor Progression and Angiogenesis in Cervical Cancer Cell (CaSki)-implanted Nude Mice - Mathuradavong, Nakorn; Srisawat, Umarat; Yoysungnoen, Bhornprom; Sookprasert, Nattapon (Asian Medical Journal and Alternative Medicine, 2022)
Introduction: Several studies have indicated that microvascular density (MVD) and the expressions of angiogenic biomarkers were associated with tumor growth and angiogenesis in cervical cancer. However, the results were incomplete and inconsistent. Objectives: To determine the correlation of the angiogenic biomarkers, including vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1-alpha (HIF-1α), cyclooxygenase-2 (COX-2), and epidermal growth factor receptor (EGFR), to tumor progression and angiogenesis in cervical cancer cell (CaSki)-implanted nude mice model. Methods: 10×106 of CaSki cells were injected into the female nude mice (n = 50) to establish subcutaneous tumors. The tumor size was measured every 3 days for one month. The MVD was evaluated using the CD31 expression. VEGF, HIF-1α, COX-2, and EGFR expression were detected by immunohistochemistry. Results: The results showed that HIF-1α (r = 0.979 and r = 0.942), VEGF (r = 0.972 and r = 0.929), COX-2 (r = 0.982 and r = 0.957), and EGFR (r = 0.993 and r = 0.971) closely correlated with tumor growth and tumor angiogenesis, respectively. Interestingly, EGFR was mostly involved in tumor growth and angiogenesis. Conclusions: This study demonstrates that the HIF-1α, VEGF, COX-2, and EGFR are a set of biological markers which are strongly related to tumor progression and angiogenesis in cervical cancer.